Agile Processes in Software Engineering and Extreme Programming - Workshops: XP 2021 Workshops, Virtual Event, June 14-18, 2021, Revised Selected Papers - Gregory, Peggy; Kruchten, Philippe (Lecture Notes in Business Information Processing, 2021)
This open access book constitutes papers from the 5 research workshops, the poster presentations, as well as two panel discussions which were presented at XP 2021, the 22nd International Conference on Agile Software Development, which was held online during June 14-18, 2021. XP is the premier agile software development conference combining research and practice. It is a unique forum where agile researchers, practitioners, thought leaders, coaches, and trainers get together to present and discuss their most recent innovations, research results, experiences, concerns, challenges, and trends. XP conferences provide an informal environment to learn and trigger discussions and welcome both people new to agile and seasoned agile practitioners. The 18 papers included in this volume were carefully reviewed and selected from overall 37 submissions. They stem from the following workshops: 3rd International Workshop on Agile Transformation 9th International Workshop on Large-Scale Agile Development 1st International Workshop on Agile Sustainability 4th International Workshop on Software-Intensive Business 2nd International Workshop on Agility with Microservices Programming